PARENTAL INVOLVEMENT AND ACHIEVEMENT MOTIVATION OF UNDERGRADUATES IN UNIVERSITY OF ILORIN - MUHAMMED, Shuaib Abolakale; MUSTAPHA, Mulikat Ladi Abdulkadir; SHITTU, Aisha Adetoun (Ilorin Journal of Education, 2023)
Neglectful parents have several negative developmental outcomes such as impulsiveness, non-compliant to rules and orders, moodiness, low in self-esteem and all of which may leads to low achievement motivation. A descriptive survey of the correlation type research design was adopted. A sample size of four hundred and twenty (420) was selected for the study using proportional and simple random sampling techniques. Data were gathered using "Parental Involvement and Achievement Motivation scales” with a reliability coefficient of 0.85 and 0.90 respectively. Data were analyzed using percentages and mean scores PPMC at 0.05 level of significance. The study revealed that respondents had positive parental involvement experiences and positive achievement motivation. It also revealed that there was a positive significant relationship between the parental involvement and achievement motivation level of respondents. Based on the findings of this study, it was concluded that adequate parental involvement is positively related with student’s achievement motivation therefore parents should be more involved in the activities of their children and facilitate their drive to succeed.